Ответы и объяснения

2012-10-03T17:25:50+00:00

(b*b+(a+b)*(a-b))/(b(a-b)²)=

(b*b+a*a-b*b)/(b(a-b)*(a+b))=

a*a/(b(a-b)²)

Лучший Ответ!
2012-10-03T17:47:20+00:00

   b                        a+b                        

_______     -     ____________  = 

(a-b)²                   b²-ab

 

       b                        a+b                  b                        a+b

= _______     -     ____________    =  _______    +     ____________    =

    (a-b)²                   b(b - a)            (a-b)²                     b(a  - b )

 

      b²     +    ( a + b)(a  - b )               b²    +      a²   - b²                            a²

= __________________________    =  _______________________    =  ________

             b(a - b)²                                        b(a - b)²                                  b(a - b)²